Students’ Mathematical Creative Thinking Skills based on Cognitive Style in Treffinger Learning with a Constructivism Approach - Maula Amalia Maghfuroh; Rochmad Rochmad; Dwijanto Dwijanto (Universitas Negeri Semarang, 2022)
This study aims to describe students' mathematical creative thinking skills based on cognitive style in Treffinger learning with a constructivism approach. The research method used was qualitative research method with descriptive approach. The subjects in this study were students of class VIII A of SMP IT Insan Cendekia in Semarang city. The subjects were selected by 3 students each based on cognitive style type field independent (FI) and cognitive style type field dependent (FD). Data collection techniques used the Group Embedded Figure Test (GEFT), interview guidelines, and observation. The results of this study indicate that students' mathematical creative thinking skills with a cognitive style type field independent (FI) has been able to meet the indicators of fluency, originality and elaboration are good, while the indicators of flexibility are quite good. In terms of students’ mathematical creative thinking skills with a cognitive style type field dependent (FD) has been able to meet the indicators of fluency are good, the indicators of originality and elaboration are quite good, while the indicators of flexibility are less good.